Pengaruh Brand Ambassador, Layanan Cash On Delivery, Dan Online Customer Review Terhadap Keputusan Pembelian Situs Shopee Generasi Z Di Kota Surakarta - Nabila Adillati Azka (Jurnal Visi Manajemen, 2023)
This study aims to understand the influence of brand ambassadors, cash-on-delivery services, and online customer reviews on the purchase choice of generation Z shopee sites in Surakarta City. For this study brand ambassadors (X1), cash on delivery services (X2), and online customer reviews (X3) are used as independent variables, while purchasing decisions (Y) are used as the dependent variable. Shopee users in Surakarta City who belong to the z generation and aged 10 to 24 years make up the population. With a sample of 100 respondents, simple random sampling was used as a sampling method. Multiple linear regression analysis is used for statistical data analysis techniques.